New Definitions for the Notions “Asset” and “Liability” in the Conceptual Framework for Financial Reporting: Reasons and Consequences - SHKULIPA, L. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2020)
The purpose of this article is to investigate the evolutionary logic of defining assets and liabilities under the influence of changes in the Conceptual Framework of Financial Reporting, the causes, and consequences of these changes in a consistent understanding by developers and practitioners. The evolutionary changes in the definitions of assets and liabilities in the Conceptual Framework of Financial Reporting and the reasons that led to these changes have been investigated. The reasons are different interpretations of probability and expected benefits; and asymmetric asset and liability identification. The expediency of interpreting an asset as a current economical resource that is controlled by an entity as a result of past events and the obligation as a current obligation of the entity to transfer an economic resource as a result of past events have been interpreted. Found different formulations of these interpretations encourage a rethinking of past practices and move towards the symmetry of assets and liabilities identification. The new criterion for defining obligatory such as “no practical ability to avoid” complicates the goal of changes because it requires the use of additional valuation judgments in practice. Understanding of the probability threshold before and after changes in asset and liabilities definitions has been examined. It was found that the old asset and liabilities definitions have no bearing on the judgment as to whether the asset existence. Participants use a higher probability threshold in assets recognition than in liabilities recognition. The implications of the changes for a consistent understanding between setters and practitioners have been identified. In particular, new changes in asset and liability definitions improve the implementation of the IASB goals and better align participants’ judgments with setters’ intentions. It is established that IFRS is now sufficiently complete to cover virtually all transactions and events within the scope of the direct standard, although it does not exclude the need to use the Conceptual Framework not only by the standards setters but also by experts, auditors, lawyers, scholars and economic students on economic faculties.